A missing link: The interdependence between sugar-sweetened beverage and cigarette consumption from China - Lu Liu; Kevin Chen (PLoS ONE, 2025)
Sugar-sweetened beverages (SSBs) and cigarettes are addictive substances and addictive substances are often related in consumption with each other. However, the potential interdependence between SSB and cigarette consumption has not been explored in the literature. As SSB and cigarette consumption have posed a great threat to individual health, the knowledge of such interdependence is critical for policymakers to design and coordinate government interventions. We thus employed Heckman sample selection model and simultaneous equation model to identify and validate the interdependence between SSB and cigarette consumption across subgroups exhibiting different smoking behaviors with individual-level data from the China Health and Nutrition Survey (CHNS) during the period from 2004 to 2011. We find that SSBs and cigarettes are complements in that individuals who ever smoked are more likely to consume SSBs frequently with higher level of SSB intake eventually and SSB intake of current smokers increases along with the amount of cigarettes smoked. SSBs and cigarettes are also substitutes in that former smokers are more likely to consume SSBs compared with current smokers. The complementary relation observed among current smokers implies that government interventions targeting one of the two goods may yield a double dividend effect on health whereas the substitutable relation displayed by former smokers suggests that the health effect of interventions designed to reduce the consumption of one good may be tempered by an elevated demand for the other.